Preparation method of degradable TWIP steel medical material for clip
By preparing Fe-Mn-Al-Ge-X alloys and employing vacuum arc melting and multi-pass processing techniques, the mechanical strength and degradation rate issues of TWIP steel medical materials were resolved, enabling the preparation of high-performance biodegradable clip materials suitable for the biomedical field.
Patent Information
- Application Number
- CN202310887527.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2026-01-02
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The lack of existing technologies for preparing TWIP steel medical materials for biodegradable clips and the corresponding performance research results in low mechanical strength, slow degradation rate, and impact on magnetic resonance imaging of pure iron.
TWIP steel medical materials are prepared using Fe-Mn-Al-Ge-X alloy through processes such as vacuum arc melting, rotary forging, extrusion and rolling. Functional elements such as Cu, Ag and Zn are added to form a biodegradable clip with excellent plasticity and degradation properties.
The prepared TWIP steel medical material has higher mechanical properties, a degradation rate that better conforms to wound healing, excellent blood compatibility and antibacterial properties, and is suitable for biomedical materials.
Smart Images

Figure CN116926405B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of biomedical metals, and particularly relates to a preparation method of TWIP steel medical material for degradable clamps. BACKGROUND
[0002] Iron-based alloys have important application prospects in the medical field such as bone tissue fixation, cardiovascular stents, and degradable clips (staplers) due to their good mechanical properties, biocompatibility, and degradability. For the application of intestinal staplers (staple and staple cartridge shell sleeve), the raw materials need to be subjected to large plastic deformation (stamping and curling) during the manufacturing process, so the raw materials must have excellent mechanical strength, in addition to good formability and ductility. Pure iron, as a material with excellent ductility, can meet the requirements of formability. Meanwhile, pure iron stents implanted in the aortas of rabbits and small pigs were found to have good biocompatibility and non-toxic degradation effects. However, pure iron has low mechanical strength, especially elongation. At the same time, the corrosion rate of biodegradable pure iron implants is very low, and it takes up to two to three years to completely degrade. In addition, the paramagnetic characteristics of pure iron interfere with the late magnetic resonance imaging. Manganese (Mn) alloying has been proven to be a better method, as Fe-Mn alloys are non-magnetic and have faster degradation rates than pure iron. And with the increase of Mn content, the degradation rate increases and the paramagnetism weakens. In order to improve the plastic deformation ability of Fe-Mn alloys, the addition of silicon (Si) elements with high biocompatibility can obtain excellent shape memory performance, mechanical strength, and faster degradation rate, and is expected to become a substitute for nickel-titanium alloys due to its low cost, significantly better weldability, and cold working performance. The addition of aluminum (Al) to FeMnSi alloys can improve their shape memory behavior, and with the increase of Al content, the plasticity of FeMnSi alloys increases, thereby improving the shape recovery deformation, thus confirming that FeMnAlSi alloys have a significant twinning-induced plasticity (TWIP) effect under tensile deformation. Although excessive Al can cause nervous system disorders, interfere with human thinking, and even cause Alzheimer's disease in severe cases, due to the relatively slow degradation rate of iron-based alloys and the low addition amount, the release amount is low. At the same time, in the application of cholangioenterostomy, in addition to part of the Al being absorbed by the human body, most of the Al is mainly excreted through the digestive tract with feces, so it will not cause excessive intake. Germanium (Ge) elements, which are in the same group as Si, can also exhibit some of the characteristics of Si, and Ge elements also have good biocompatibility and biological functionality. They have important applications in cancer, inflammation, oxidation, radiation protection, and immune function promotion therapies. Therefore, FeMnAlGe alloys are expected to be the research direction of high-strength and ductility iron-based alloys. In order to adapt to different application environments (cholangioenterostomy, blood vessels, and skin) of degradable clips (staplers), a series of functional FeMnAlGe alloys need to be developed, and the FeMnAlGe alloys are further functionalized and strengthened by adding functional / strengthening elements.
[0003] At present, the preparation method and the corresponding performance of the degradable TWIP steel medical material for degradable clamps have not been reported in the domestic and foreign literatures, so the degradable Fe-Mn-Al-Ge-X medical material is proposed to be used as the material of the degradable clamp in the next stage. SUMMARY
[0004] In view of the problems in the prior art, the present application provides a preparation method of a TWIP steel medical material for degradable clamps to solve the above problems.
[0005] The technical scheme of the present application is as follows: a preparation method of a TWIP steel medical material for degradable clamps, the TWIP steel medical material comprises the following components in percentage by mass: Mn: 30-40%, Al: 3-6%, Ge: 3-6%, X: 0-2%, and the balance is Fe, and X is one or more of Cu, Ag, Zn, Ca, Sr, Li, Ti, Zr, Au and Mg.
[0006] Further, the composition of the TWIP steel medical material raw material comprises the following components: high-purity iron block (99.99%), pure manganese block, pure aluminum particles (99.99%), single-crystal germanium particles (99.999%) and X metal particles / block (99.99%).
[0007] Further, the preparation method of the TWIP steel medical material for degradable clamps comprises the following steps:
[0008] a. taking high-purity iron block, pure manganese block, pure aluminum particles, single-crystal germanium particles and X metal particles / block as raw materials;
[0009] b. mixing according to the burn loss rate and the Fe-Mn-Al-Ge-X mass percentage, then placing in a water-cooled copper crucible and placing in a vacuum arc melting furnace;
[0010] c. starting the mechanical pump and the molecular pump in the vacuum arc melting furnace, and after the vacuum degree in the vacuum arc melting furnace is reduced to 1-10*10 -3 Pa, introducing argon with a purity of 99.99% to make the argon pressure rise to 10-100kPa, and then heating the water-cooled copper crucible containing the raw materials under argon protection and setting the melting temperature to 1200-1600℃ to form a steel liquid by melting;
[0011] d. after the steel liquid is fully melted, continuing to heat for 2-10min and repeatedly remelting five times by arc;
[0012] e. sucking the steel liquid into a 20cm*2cm*2cm high-purity graphite mold in the furnace;
[0013] f. Then, after the graphite mold is cooled to room temperature, the Fe-Mn-Al-Ge-X alloy ingot is taken out.
[0014] Further, the method further comprises the following steps:
[0015] g. The ingot is placed in a muffle furnace heated to 900-1100°C for 2-10 hours for homogenization annealing, and then water-cooled / air-cooled to obtain a cast Fe-Mn-Al-Ge-X sample;
[0016] h. The cast sample is placed in a muffle furnace and heated to 1000-1200°C, and then held for 0.5-3 hours;
[0017] i. The cast sample is taken out and hot swaged at a feed rate of 5-10% per pass to 50-70% of the original thickness, and then held for 5-10 minutes between every two passes;
[0018] j. After the end, the swaged Fe-Mn-Al-Ge-X sample is obtained by cooling to room temperature in water;
[0019] k. A strip sample with a thickness of 10 cm x 1 cm x 1 cm is cut from the swaged sample, and a 120° equal-angle extrusion (ECAP) mold containing the strip sample is extruded to obtain an ECAP Fe-Mn-Al-Ge-X sample.
[0020] l. A rolled Fe-Mn-Al-Ge-X foil is prepared;
[0021] m. The Fe-Mn-Al-Ge-X foil is punched into anastomosis nails with short spikes using a punch machine, and the excess foil is coiled into a tube with a diameter of 2-3 mm, and then welded using a laser welding machine;
[0022] n. The anastomosis nails and the tube are assembled into a degradable clip.
[0023] Further, in step k, the extrusion step is:
[0024] Step one, the 120° equal-angle extrusion (ECAP) mold containing the strip sample is placed in a muffle furnace heated to 400-600°C for 0.1-1 hours;
[0025] Step two, the ECAP treatment is performed 1-5 times on a 600-ton extruder at an extrusion speed of 0.5-1 mm / s, and the heating temperature, heating time, extrusion direction and angle of the sample are consistent for each pass;
[0026] Step three, after complete extrusion, the ECAP Fe-Mn-Al-Ge-X sample is obtained by quickly placing it in liquid nitrogen for deep cooling treatment and cooling to room temperature.
[0027] Further, in step l, the preparation step of the rolled Fe-Mn-Al-Ge-X foil material is:
[0028] Step one, polish the ECAP state Fe-Mn-Al-Ge-X sample to remove the oxide skin;
[0029] Step two, cut a 10cm*1cm*2mm thin sheet along the length direction of the ECAP state Fe-Mn-Al-Ge-X sample;
[0030] Step three, cold roll to a foil material with a thickness of 0.1-0.3mm by adopting a reduction of 2-5% per pass;
[0031] Step four, place the foil material obtained in step three into a muffle furnace with a temperature of 700-900℃ for 2-30min, then quickly place it into liquid nitrogen for cryogenic treatment and cool to room temperature to obtain the rolled Fe-Mn-Al-Ge-X foil material.
[0032] The beneficial effects of the present application are:
[0033] 1, the prepared degradable TWIP steel medical material has higher mechanical properties, a more compatible degradable plastic with wound healing, more excellent blood compatibility, cell compatibility and antibacterial performance, and is expected to become a potential degradable biomedical material;
[0034] 2, the adjustment of Al and Ge content and the addition of X element effectively play the role of alloy strengthening and functionalization. BRIEF DESCRIPTION OF DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings needed to be used in the embodiments or prior art description will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can also be obtained by those skilled in the art without creative labor.
[0036] Figure 1 Fe-35Mn-4Al-4Ge-2Ag foil material physical map for the specific embodiment of the present application;
[0037] Figure 2 XRD pattern of Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foil material for the specific embodiment of the present application;
[0038] Figure 3 Metallographic structure diagram of Fe-35Mn-4Al-4Ge-2Ag foil material for the specific embodiment of the present application;
[0039] Figure 4For the specific embodiment of the present application, the cell survival rate of L929 cells after 3 days of culturing on the surface of Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foil;
[0040] Figure 5 For the specific embodiment of the present application, the bacteriostatic circle diameter of E. coli after 1 day of co-culturing with Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foil. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.
[0042] In the description of the present application, it should be noted that the terms used herein are only for describing the specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. For the convenience of description, the sizes of the parts shown in the drawings are not drawn in accordance with the actual proportional relationship. The techniques, methods and devices known to those of ordinary skill in the relevant art can not be discussed in detail, but should be considered as part of the authorized description under appropriate circumstances. In all examples shown and discussed herein, any specific value should be interpreted as merely exemplary, and not as a limitation. Therefore, other examples of exemplary embodiments can have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.
[0043] As Figures 1 to 5 shown in FIG. 1, Example 1, high-purity iron blocks (99.99%), pure manganese blocks, pure aluminum particles (99.99%), single-crystal germanium particles (99.999%), and silver particles (99.99%) were used as raw materials. After mixing according to the burn loss rate and according to the mass percentage of Fe-(35wt.%)Mn-(4wt.%)Al-(4wt.%)Ge-(2wt.%)Ag, the mixture was placed in a water-cooled copper crucible and placed in a vacuum arc melting furnace.
[0044] First, the mechanical pump and the molecular pump are started, and when the vacuum degree in the vacuum arc melting furnace is reduced to 3*10-3 Pa, argon gas with a purity of 99.99% is introduced to make the argon pressure rise to 60 kPa. Then, the water-cooled copper crucible containing raw materials is heated by arc under the protection of argon, and the melting temperature is set to 1300°C. After the steel liquid is fully melted, arc heating is continued for 5 min and repeated remelting for five times. The Fe-35Mn-4Al-4Ge-2Ag alloy ingot is suction cast in a high-purity graphite mold with a size of 20 cm*2 cm*2 cm, and finally, the pressure is released after air cooling to room temperature.
[0045] First step: The ingot is put into a muffle furnace heated to 1000°C for homogenization annealing for 8 h and then water-cooled to eliminate composition segregation and stabilize the structure and obtain the as-cast Fe-35Mn-4Al-4Ge-2Ag sample.
[0046] Second step: The as-cast sample is placed in a muffle furnace and heated to 1100°C, and then held for 1 h. The hot rotary swaging is performed with a feed rate of 5% per pass to 60% of the original thickness, and the sample is held for 10 min after every two passes. Finally, the swaged Fe-35Mn-4Al-4Ge-2Ag sample is obtained after cooling to room temperature in water.
[0047] Third step: A strip sample with a size of 10 cm*1 cm*1 cm is cut from the swaged sample. The 120° equal-angle extrusion (ECAP) die containing the strip sample is placed in a muffle furnace heated to 500°C for 0.5 h, and then the ECAP process is performed on a 600-ton extruder at an extrusion speed of 1 mm / s for 3 passes. The heating temperature, heating time, extrusion direction, and angle of the sample are consistent in each pass. After complete extrusion, the sample is quickly placed in liquid nitrogen for deep cooling to room temperature to obtain the ECAP Fe-35Mn-4Al-4Ge-2Ag sample.
[0048] Fourth step: After removing the oxide skin by surface grinding, a 10 cm*1 cm*2 mm thin sheet is cut along the length direction. The sheet is cold-rolled to a thickness of 0.2 mm with a reduction of 5% per pass. Then, the sample is placed in a muffle furnace at a temperature of 800°C for 5 min, and then quickly placed in liquid nitrogen for deep cooling to room temperature to obtain the rolled Fe-35Mn-4Al-4Ge-2Ag foil. Deep cooling can significantly improve the dimensional stability and release thermal stress of the foil.
[0049] The same processing method is used to prepare Fe-35Mn-4Al-4Ge foil.
[0050] Fifth step: punch the Fe-35Mn-4Al-4Ge-2Ag foil into anastomosis nails with short spikes using a punch machine, and then roll the excess foil into a tube with a diameter of 2.5 mm, and finally weld the tube using a laser welding machine. The anastomosis nail and the tube are combined to form a degradable clip.
[0051] In addition, the foil can be punched into anastomosis nails of different specifications, the excess foil is rolled into a tube of corresponding size, and then assembled into a degradable clip for application in different environments (biliary intestine, blood vessels, skin).
[0052] The X-ray fluorescence spectrometer test results show that the Fe-35Mn-4Al-4Ge-2Ag foil contains 34.93% Mn, 4.18% Al, 3.93% Ge, and 1.97% Ag, with the rest being Fe. The Fe-35Mn-4Al-4Ge foil contains 34.86% Mn, 4.03% Al, and 3.96% Ge, with the rest being Fe.
[0053] Figure 2 The X-ray diffraction test results of the Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foils show that both foils are composed of non-magnetic γ-Fe (austenite) phase, which does not interfere with the post-anastomosis nuclear magnetic resonance imaging detection.
[0054] Figure 3 The metallographic structure of the Fe-35Mn-4Al-4Ge-2Ag foil is shown in the figure. The Fe-35Mn-4Al-4Ge-2Ag foil contains equiaxed γ-Fe phase with an average grain size of 9.5 μm. The foil tensile samples were prepared according to GB / T 228.1-2010 "Metallic Materials Tensile Test Part 1, Room Temperature Test Method", and the tensile test was performed at room temperature using a universal testing machine with a crosshead moving speed of 1 mm / min and a non-clamping tensile clamp. Table 1
[0055]
[0056] As shown in the tensile mechanical properties and Vickers hardness results of the Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foils in Table 1, the tensile yield strength of the Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foils is 363 MPa and 477 MPa, respectively, the tensile strength is 876 MPa and 989 MPa, respectively, the elongation is 65.3% and 74.6%, respectively, and the strength plastic product is 57.2 GPa% and 73.8 GPa%, respectively. In addition, the Vickers hardness of the Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foils is 375 HV and 429 HV, respectively.
[0057] The electrochemical corrosion results of Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foils in Hanks' simulated body fluid (8.0 g / L NaCl, 0.350 g / L NaHCO3, 0.4 g / L KCl, 0.023 g / L Na2HPO4, 0.060 g / L KH2PO4, 0.047 g / L MgCl2, 0.029 g / L MgSO4, 0.14 g / L CaCl2, 1.0 g / L glucose, adjusted to pH 7.4 with 1 N NaOH or 1 N HCl) and FaSSIF simulated intestinal fluid (0.42 g / L NaOH, 3.95 g / L NaH2PO4-H2O, 6.19 g / L NaCl, 2.24 g FaSSIF powder completely dissolved, adjusted to pH 6.5 with 1 N NaOH or 1 N HCl) at a test temperature of 37 °C are shown in Table 2. The electrochemical performance parameters of Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foils in Hanks' and FaSSIF solutions after polarization test are shown in Table 2.
[0058] Table 2
[0059]
[0060] The corrosion potential of Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foils in Hanks' solution were -0.693 V and -0.684 V, the corrosion current density were 44.3 A / cm2and 50.8 A / cm2, and the corrosion rate were 533 μm / y and 612 μm / y, respectively. In FaSSIF simulated intestinal fluid, the corrosion potential were -0.656 V and -0.642 V, the corrosion current density were 62.8 mA / cm2and 80.6 mA / cm2, and the corrosion rate were 756 μm / y and 971 μm / y, respectively. The degradation rate of Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foils after 30 days immersion in Hanks' solution were 87 μm / y and 98 μm / y, and in FaSSIF simulated intestinal fluid were 139 μm / y and 204 μm / y, respectively.
[0061] Therefore, the Fe-35Mn-4Al-4Ge-2Ag foil has a faster degradation rate in the FaSSIF simulated intestinal fluid, and can be degraded faster and discharged out of the body after wound healing. The hemolysis rates of the Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foil extracts in the rat blood are 4.2% and 3.3%, respectively, which meet the requirement that the hemolysis rate of a clinical medical material is less than 5%, and exhibit good blood compatibility.
[0062] Figure 4 After the L929 cells are directly cultured on the Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foil surfaces for 3 days, the cell survival rates are 85.3% and 93.9%, respectively, and according to the ISO 10993-5 standard, the Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foils both exhibit no cytotoxicity. In addition, Figure 5 After the Fe-35Mn-4Al-4Ge and Fe-35Mn-4Al-4Ge-2Ag foils are co-cultured with E. coli for 1 day, the bacteriostatic circle sizes are 1.4 mm and 4.2 mm, respectively, and both have good antibacterial effect. Therefore, the Fe-35Mn-4Al-4Ge-2Ag has higher mechanical properties, a degradation rate more suitable for wound healing, better blood compatibility, cell compatibility and antibacterial properties than the Fe-35Mn-4Al-4Ge, which indicates that the addition of Ag plays a role in alloy strengthening and functionalization.
[0063] Example 2
[0064] High-purity iron blocks (99.99%), pure manganese blocks, pure aluminum particles (99.99%), single-crystal germanium particles (99.999%) and Ag metal particles (99.99%) are used as raw materials, and are mixed according to the burn loss rate and in the mass percentage of Fe-(35wt.%)Mn-(3wt.%)Al-(6wt.%)Ge-(2wt.%)Ag, and then are placed into a water-cooled copper crucible and are placed in a vacuum arc melting furnace.
[0065] First, the mechanical pump and the molecular pump are started, and after the vacuum degree in the vacuum arc melting furnace is reduced to 1x10-3Pa, argon with a purity of 99.99% is introduced, so that the argon pressure is increased to 50kPa. Then, the water-cooled copper crucible containing the raw materials is heated by arc under argon protection, and the melting temperature is set to 1300℃. After the steel liquid is fully melted, the arc is continued to heat for 10min and is repeatedly remelted five times, and is suction cast into a 20cmx2cmx2cm high-purity graphite mold in the furnace. Finally, after air cooling to room temperature, the pressure is released and the Fe-35Mn-3Al-6Ge-2Ag alloy ingot is taken out.
[0066] First step: The ingot was put into a muffle furnace heated to 950℃ for homogenization annealing for 8h and water cooling to eliminate composition segregation and stabilize the microstructure and obtain the as-cast Fe-35Mn-3Al-6Ge-2Ag sample.
[0067] Second step: The as-cast sample was put into a muffle furnace heated to 1050℃ and held for 1h, then hot swaged by 10% of the feed amount per pass to 50% of the original thickness and held for 10min every two passes, and finally cooled to room temperature in water to obtain the wrought Fe-35Mn-3Al-6Ge-2Ag sample.
[0068] Third step: A strip sample with a thickness of 10cm x 1cm x 1cm was cut from the wrought sample, and a 120° equal-angle extrusion (ECAP) die containing the strip sample was put into a muffle furnace heated to 550℃ and held for 0.5h, then ECAP processing was performed on a 600-ton extruder at an extrusion speed of 1mm / s for 4 passes with the same heating temperature, heating time, extrusion direction and angle for each pass, and after complete extrusion, the sample was quickly placed in liquid nitrogen for deep cooling to room temperature to obtain the ECAP Fe-35Mn-3Al-6Ge-2Ag sample.
[0069] Fourth step: After removing the oxide skin by surface grinding, a 10cm x 1cm x 2mm thin sheet was cut along the length direction, cold rolled to a thickness of 0.2mm with a reduction of 2% per pass, then placed in a muffle furnace at a temperature of 800℃ for 15min, and finally quickly placed in liquid nitrogen for deep cooling to room temperature to obtain the rolled Fe-35Mn-3Al-6Ge-2Ag foil.
[0070] Fifth step: The Fe-35Mn-3Al-6Ge-2Ag foil was punched into anastomosis pins with short spikes on the head by a punch machine, and the excess foil was coiled into a tube with a diameter of 2.5mm and welded using a laser welding machine, and finally the anastomosis pins and tube were combined to assemble a degradable clamp.
[0071] The X-ray fluorescence spectrometer test showed that the Fe-35Mn-3Al-6Ge-2Ag foil contained 35.11% Mn, 3.08% Al, 5.97% Ge, 1.95% Ag, and the rest was Fe. The tensile yield strength, tensile strength, elongation and Vickers hardness of the Fe-35Mn-3Al-6Ge-2Ag foil were 493MPa, 1026MPa, 53.6%, 55.0GPa% and 403HV, respectively.
[0072] The corrosion potential of the Fe-35Mn-3Al-6Ge-2Ag foil in Hanks' simulated body fluid and FaSSIF simulated intestinal fluid was -0.676 V and -0.625 V, respectively, the corrosion current density was 47.5 A / cm2and 73.2 A / cm2, respectively, and the corrosion rate was 572 μm / y and 881 μm / y, respectively.
[0073] The degradation rate of the Fe-35Mn-3Al-6Ge-2Ag foil after immersion in Hanks' solution and FaSSIF simulated intestinal fluid for 30 days was 92 μm / y and 183 μm / y, respectively.
[0074] The hemolysis rate of the Fe-35Mn-3Al-6Ge-2Ag foil extract in rat blood was 3.0%, which met the requirement of a hemolysis rate of less than 5% for clinical medical materials, and the Fe-35Mn-3Al-6Ge-2Ag foil exhibited good blood compatibility.
[0075] The cell survival rate of L929 cells cultured directly on the surface of the Fe-35Mn-3Al-6Ge-2Ag foil for 3 days was 95.2%, and according to the ISO 10993-5 standard, the Fe-35Mn-3Al-6Ge-2Ag foil exhibited no cytotoxicity. In addition, the size of the bacteriostatic circle of the Fe-35Mn-3Al-6Ge-2Ag foil after co-culturing with Escherichia coli for 1 day was 4.0 mm, and the Fe-35Mn-3Al-6Ge-2Ag foil exhibited good antibacterial performance.
[0076] Therefore, the Fe-35Mn-3Al-6Ge-2Ag foil also has higher mechanical property matching, a degradation rate more suitable for wound healing, better blood compatibility, cell compatibility, and antibacterial performance than the Fe-35Mn-4Al-4Ge, indicating that the adjustment of the Al and Ge content and the addition of Ag also play a role in alloy strengthening and functionalization.
[0077] Example 3
[0078] High-purity iron blocks (99.99%), pure manganese blocks, pure aluminum particles (99.99%), single-crystal germanium particles (99.999%), and copper particles (99.99%) were used as raw materials. The raw materials were mixed according to the mass percentage of Fe-(35 wt.%) Mn-(3 wt.%) Al-(3 wt.%) Ge-(1 wt.%) Cu, and then placed in a water-cooled copper crucible and put into a vacuum arc melting furnace.
[0079] Firstly, the mechanical pump and the molecular pump were started, and when the vacuum degree in the vacuum arc melting furnace was reduced to 1*10-3 Pa, argon with a purity of 99.99% was introduced to make the argon pressure rise to 50 kPa. Then, the water-cooled copper crucible containing raw materials was heated by arc under the protection of argon, and the melting temperature was set to 1400°C. After the steel liquid was fully melted, arc heating was continued for 5 min and repeated five times. The alloy ingot was suction cast into a high-purity graphite mold with a size of 20 cm*2 cm*2 cm. Finally, the furnace was cooled to room temperature, and the Fe-35Mn-3Al-3Ge-1Cu alloy ingot was taken out after pressure relief.
[0080] First step: The ingot was put into a muffle furnace heated to 1000°C for homogenization annealing for 10 h and then water-cooled to eliminate composition segregation and stabilize the structure and obtain the as-cast Fe-35Mn-3Al-3Ge-1Cu sample.
[0081] Second step: The as-cast sample was placed in a muffle furnace and heated to 1100°C for 1 h. Then, the hot rotary swaging was performed with a feed rate of 10% per pass to reduce the thickness to 70% of the original thickness, and 10 min of heat preservation was performed every two passes. Finally, the swaged Fe-35Mn-3Al-3Ge-1Cu sample was obtained after cooling to room temperature in water.
[0082] Third step: A strip sample with a size of 10 cm*1 cm*1 cm was cut from the swaged sample. The 120° equal-angle extrusion (ECAP) die containing the strip sample was placed in a muffle furnace heated to 500°C for 0.2 h. Then, the ECAP process was performed on a 600-ton extruder at an extrusion speed of 0.5 mm / s for 4 passes, and the heating temperature, heating time, extrusion direction, and angle of the sample were consistent in each pass. After complete extrusion, the sample was quickly placed in liquid nitrogen for deep cooling to room temperature to obtain the ECAP Fe-35Mn-3Al-3Ge-1Cu sample.
[0083] Fourth step: After removing the oxide skin by surface grinding, a 10 cm*1 cm*2 mm thin sheet was cut along the length direction. The sheet was cold-rolled to a thickness of 0.2 mm with a reduction of 5% per pass. Then, the sample was placed in a muffle furnace at a temperature of 800°C for 10 min, and then quickly placed in liquid nitrogen for deep cooling to room temperature to obtain the rolled Fe-35Mn-3Al-3Ge-1Cu foil. Deep cooling can significantly improve the dimensional stability and release thermal stress of the foil.
[0084] Fifth step: The Fe-35Mn-3Al-3Ge-1Cu foil was punched into anastomosis pins with short spikes on the head using a punch machine. The excess foil was coiled into a tube with a diameter of 2.5 mm, and then welded using a laser welding machine. Finally, the anastomosis pins and the tube were combined to form a degradable clamp.
[0085] The X-ray fluorescence spectrometer test obtained that the Fe-35Mn-3Al-3Ge-1Cu foil contains 35.08% Mn, 3.03% Al, 3.02% Ge, 1.05% Cu, and the rest is Fe. The tensile yield strength, tensile strength, elongation and Vickers hardness of the Fe-35Mn-3Al-3Ge-1Cu foil are 453 MPa, 972 MPa, 69.5%, 67.5 GPa% and 413 HV, respectively.
[0086] The corrosion potential of the Fe-35Mn-3Al-3Ge-1Cu foil in Hanks' simulated body fluid and FaSSIF simulated intestinal fluid is-0.689 V and-0.647 V, respectively, the corrosion current is 51.4 A / cm2 and 82.3 A / cm2, respectively, and the corrosion rate is 619 μm / y and 990 μm / y, respectively.
[0087] The degradation rate of the Fe-35Mn-3Al-3Ge-1Cu foil after immersion in Hanks' solution and FaSSIF simulated intestinal fluid for 30 days is 102 μm / y and 210 μm / y, respectively.
[0088] The hemolysis rate of the Fe-35Mn-3Al-3Ge-1Cu foil extract in rat blood is 2.6%, which meets the requirement that the hemolysis rate of clinical medical materials is less than 5%, and exhibits good blood compatibility.
[0089] The cell survival rate of L929 cells directly cultured on the surface of the Fe-35Mn-3Al-3Ge-1Cu foil for 3 days is 93.8%, and according to the ISO 10993-5 standard, the Fe-35Mn-3Al-3Ge-1Cu foil exhibits no cytotoxicity. In addition, the bacteriostatic circle size of the Fe-35Mn-3Al-3Ge-1Cu foil after co-culturing with E. coli for 1 day is 3.2 mm, which exhibits good antibacterial effect.
[0090] Therefore, the Fe-35Mn-3Al-3Ge-1Cu foil also has higher mechanical property matching, degradation rate more suitable for wound healing, better blood compatibility, cell compatibility and antibacterial performance than Fe-35Mn-4Al-4Ge, which indicates that the adjustment of Al and Ge content and the addition of Cu also play the role of alloy strengthening and functionalization.
[0091] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a TWIP steel medical material for degradable clips, characterized by, The TWIP steel medical material comprises the following components in percentage by mass: Mn: 30-40%, Al: 3-6%, Ge: 3-6%, X: 0-2%, and the balance of Fe, wherein X is one or more of Cu, Ag, Zn, Ca, Sr, Li, Ti, Zr, Au, and Mg; The TWIP steel medical material raw material comprises the following components: high-purity iron block, pure manganese block, pure aluminum particles, single-crystal germanium particles, and X metal particles / block; The preparation method of the TWIP steel medical material for the degradable clip comprises the following steps: a. taking high-purity iron block, pure manganese block, pure aluminum particles, single-crystal germanium particles, and X metal particles / block as raw materials; b. mixing according to the burning loss rate and Fe-Mn-Al-Ge-X percentage by mass, then placing in a water-cooled copper crucible and in a vacuum arc melting furnace; c、 turn on the mechanical pump and molecular pump in the vacuum arc melting furnace, and wait for the vacuum degree in the vacuum arc melting furnace to decrease to (1-10) × 10 -3 After 1 Pa, the argon gas with a purity of 99.99% is introduced to make the argon pressure increase to 10-100 kPa, and then the water-cooled copper crucible containing raw materials is heated by arc under the protection of argon, and the melting temperature is set to 1200-1600℃, and the molten steel is formed by melting. d. after the steel liquid is fully melted, continuing heating for 2-10 min by using an electric arc and repeatedly remelting for five times; e. sucking the steel liquid into a 20 cm×2 cm×2 cm high-purity graphite mold in the furnace; f. then air cooling / furnace cooling the graphite mold to room temperature, then unloading and taking out the Fe-Mn-Al-Ge-X alloy ingot; g. placing the ingot in a muffle furnace heated to 900-1100℃ for homogenization annealing for 2-10 h, then water cooling / air cooling to obtain a cast Fe-Mn-Al-Ge-X sample; h. placing the cast sample in a muffle furnace and heating to 1000-1200℃, then holding for 0.5-3 h; i. taking out the cast sample and hot swaging by 5-10% of the original thickness 50-70% with a swaging feed rate of 5-10% per pass, and then holding for 5-10 min every two passes; j. after the end, placing in water and cooling to room temperature to obtain a wrought Fe-Mn-Al-Ge-X sample; k. cutting a 10 cm×1 cm×1 cm strip sample from the wrought sample, and then extruding the 120° equal-angle extrusion (ECAP) mold containing the strip sample to obtain an ECAP Fe-Mn-Al-Ge-X sample; l. preparing a rolled Fe-Mn-Al-Ge-X foil; m. stamping the Fe-Mn-Al-Ge-X foil into an anastomosis nail with a short spike on the head by using a punch, and then curling the excess foil into a 2-3 mm diameter tube, and then welding by using a laser welding machine; n. assembling the anastomosis nail and the tube into a degradable clip.
2. A method of preparing a TWIP steel medical material for degradable clips according to claim 1, characterized in that, In step k, the extrusion step is as follows: Step one, placing the 120° equal-angle extrusion (ECAP) mold containing the strip sample in a muffle furnace heated to 400-600℃ and holding for 0.1-1 h; Step two, performing ECAP processing on a 600 ton extruder at an extrusion speed of 0.5-1 mm / s for 1-5 times, and the heating temperature, heating time, extrusion direction, and angle of the sample are consistent every pass; Step three, after complete extrusion, quickly placing in liquid nitrogen for deep cooling treatment and cooling to room temperature to obtain an ECAP Fe-Mn-Al-Ge-X sample.
3. A method of preparing a TWIP steel medical material for degradable clips according to claim 1, characterized in that, In step l, the preparation step of the rolled Fe-Mn-Al-Ge-X foil is as follows: Step one, polishing the ECAP Fe-Mn-Al-Ge-X sample to remove the oxide skin; Step two, cutting a 10cm×1cm×2mm thin slice along the length direction of the ECAP Fe-Mn-Al-Ge-X sample; Step three, cold rolling with a reduction of 2-5% per pass to a thickness of 0.1-0.3mm; Step four, placing the foil obtained in step three into a muffle furnace at a temperature of 700-900℃ for 2-30min, and then quickly placing it into liquid nitrogen for deep cooling to room temperature to obtain the rolled Fe-Mn-Al-Ge-X.
Citation Information
Patent Citations
Medical degradable Fe-Mg-Ag alloy material, preparation and application
CN108677099A
Anastomosing nail material capable of degrading Mg-Zn-Ca-M in organism, and preparation method thereof
CN109972007A
Bioresorbable pseudoelastic fe-mn-x-y alloys for medical implants
WO2021165333A1